2019
DOI: 10.1186/s12941-018-0302-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypervirulent Klebsiella pneumoniae (hypermucoviscous and aerobactin positive) infection over 6 years in the elderly in China: antimicrobial resistance patterns, molecular epidemiology and risk factor

Abstract: BackgroundThe definition of hypervirulent Klebsiella pneumoniae (hvKp), traditionally regarded as hypermucoviscosity, is controversial. However, data based on both phenotype (hypermucoviscous) and genetic (aerobactin) criteria are limited.MethodsA retrospective study was conducted in 175 geriatric patients between January 2008 and January 2014. The clinical and molecular data, including antimicrobial susceptibility testing, extended-spectrum-β-lactamase (ESBL) production, virulence gene, and multilocus sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 40 publications
8
91
5
Order By: Relevance
“…Patients with hvKp tend to be younger, immunocompetent, present with severe disease compared to cKp [30,51] and present from community settings [9,38,51,58]. Diabetes is a significant risk factor for acquiring a hvKp infection as opposed to a cKp infection [58][59][60][61][62], and for developing metastatic complications in patients with a liver abscess [40,63,64]. However, not all studies have consistently found this association [6,51], suggesting the connection between diabetes and hvKp could vary by region or clinical presentation.…”
Section: Clinical Presentation and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with hvKp tend to be younger, immunocompetent, present with severe disease compared to cKp [30,51] and present from community settings [9,38,51,58]. Diabetes is a significant risk factor for acquiring a hvKp infection as opposed to a cKp infection [58][59][60][61][62], and for developing metastatic complications in patients with a liver abscess [40,63,64]. However, not all studies have consistently found this association [6,51], suggesting the connection between diabetes and hvKp could vary by region or clinical presentation.…”
Section: Clinical Presentation and Risk Factorsmentioning
confidence: 99%
“…Historically, antimicrobial resistance was rare with only 2% of isolates exhibiting resistance to tested first generation cephalosporins in Taiwan from 1997 to 2005 [6]. However, the prevalence of multidrug-resistant hvKp is increasing, possibly related to the increase in healthcare-associated infections, making this already morbid infection more difficult to treat [9,10,12,55,56,58,60,69]. Carbapenem-resistant infections are the most concerning of the multidrug-resistant hvKp isolates, and the optimal treatment is still unknown.…”
Section: Outcomes and Treatment Of Hvkpmentioning
confidence: 99%
“…A retrospective study was conducted from February 2018 to June 2019 in the First A liated Hospital of Chongqing Medical University, a 3200-bed tertiary teaching hospital. First, a total of 613 consecutive cases of cKP infection were enrolled during the study period, of which 135 were de ned as hvKP with positive for both string test and aerobactin gene, as has been described previously [19]. Second, according to the prognosis of hospitalization, 135 patients with hvKP were divided into survival group and death group to determine the prognostic factors related to in-hospital mortality of hvKP infection (Fig.…”
Section: Study Design and De Nitionmentioning
confidence: 99%
“…Several outbreaks of K. pneumoniae infections have been reported in hospital settings from different countries, including China, Israel, Poland, Italy, Colombia, and the United States (Kaye and Dhar, 2016;Ocampo et al, 2016;Baraniak et al, 2017;Krapp et al, 2018;Sotgiu et al, 2018;Liu and Guo, 2019). Reportedly, K. pneumoniae accounts for ∼12% of all hospital-acquired pneumonia in the world (Ashurst and Dawson, 2019).…”
Section: Introductionmentioning
confidence: 99%